2020
DOI: 10.4314/jasem.v23i12.12
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Production of Injection Moulded Polyvinylchloride--Sawdust Composite

Abstract: This study focused on the modeling and production of the injection moulded Polyvinylchloride-Sawdust (PVC-sawdust) composite. The PVC material and sawdust were mixed together to form a homogenous mixture with various percentage composition by volume as recommended by the central composite design (CCD). The two screw plunger injection moulding machine with maximum clamping force of 120 tons and shot capacity of 3.0oz was used to produce Polyvinylchloride-Sawdust (PVC-Sawdust) composite at various temperature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The tensile strength decreased by as much as 14.3% from the third cycle to the seventh cycle. Aliyegbenoma and co‐workers [ 86 ] studied both the modeling and production of the injection molded polyvinyl chloride (PVC) reinforced with sawdust composite. The role and/or influence of temperature, material, and percentage (by volume) of the constituents on mechanical properties of the engineered composite was determined using response surface methodology (RSM).…”
Section: Mechanical Characterization Of the Injection Molded Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile strength decreased by as much as 14.3% from the third cycle to the seventh cycle. Aliyegbenoma and co‐workers [ 86 ] studied both the modeling and production of the injection molded polyvinyl chloride (PVC) reinforced with sawdust composite. The role and/or influence of temperature, material, and percentage (by volume) of the constituents on mechanical properties of the engineered composite was determined using response surface methodology (RSM).…”
Section: Mechanical Characterization Of the Injection Molded Compositesmentioning
confidence: 99%
“…From the third cycle to the fourth cycle, flexural strength of the composite decreased from 40 to 36 MPa and modulus of the composite decreased from 4763 to 4589 MPa. Aliyegbenoma and co‐workers [ 86 ] studied the effect of an interaction of test temperature, volume of material, and material type on mechanical properties of the PVC/sawdust composite using the approach of RSM. The maximum value of flexural strength was 61.41 MPa, and the elastic modulus was 3.42 GPa at a temperature of 224.65°C and polymer quantity of 61.46%.…”
Section: Mechanical Characterization Of the Injection Molded Compositesmentioning
confidence: 99%
“…Aliyegebenoma at al. [107], reported the mechanical properties of polyvinylchloridesawdust (PVC-sawdust) composite using injection mold process. It was revealed that the tensile strength, proof strength, flexural modulus of PVC-sawdust composite was maximized with 43.7 MPa, 48.4 MPa, 61.4 MPa and 3.42 GPa at temperature 224.65 • C and 61.5% polymer level.…”
Section: Polyvinyl Chloride (Pvc)mentioning
confidence: 99%
“…Oilseed fibers showed superior mechanical properties due to their high aspect ratio and chemical characteristics. Aliyegebenoma et al [5] focused on the modeling and production of the injection molded Polyvinylchloride-Sawdust (PVC-sawdust) composite. The results for PVC-Sawdust composite showed that the tensile strength, proof stress, flexural strength and flexural modulus were maximized at barrel temperature of 224.65 ℃ and polymer level of 61.46% respectively the coefficient of determination (R2) obtained ranged from 0.9213 (92.13%) to 0.981 (98.10%).…”
Section: Introductionmentioning
confidence: 99%